ANALISIS PENGARUH TINGKAT PENGANGGURAN TERBUKA DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP TINGKAT KEMISKINAN DI KABUPATEN/KOTA PROVINSI JAWA BARAT PERIODE TAHUN 2020-2021 - Novdwikaputri, Fariza (Universitas Maritim AMNI Semarang, 2022)
Poverty is a problem that exists in every region. Many factors can affect the level of poverty, for example, the unemployment rate and also the Human Development Index. The higher the unemployment rate, the higher the poverty rate will be. And also if the higher the Human Development Index, the lower the poverty rate. This study aims to determine whether the Open Unemployment Rate and the Human Development Index affect the Poverty Level. This research is a quantitative research. The variables used in this study are the Open Unemployment Rate, the Human Development Health Index, and the Poverty Level. The analysis used is a panel data method in the form of a cross section of 27 regencies/cities in West Java Province and time series data from 2020 - 2021.